(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
The efficacy and effects of two biological insecticides, NeemAzal T/S® and Pyrethrum FS EC, applied individually and in combination with Polyversum (a biological growth regulator and fungicide) and Biofa (an organic foliar fertilizer), in controlling Acyrthosyphon pisum population density were studied. Nurelle D (a synthetic insecticide), applied alone and in combination with Flordimex 420 (a synthetic growth regulator), was used as a standard. The products were applied once (at budding stage) or twice (at budding and flowering stages). Twenty-four variants were studied. The interaction of Pyrethrum with Biofa was the most efficient variant of the biological products, causing a reduction in aphid density that reached 48.2% after double treatment, while Pyrethrum+Polyversum (42.5%) was the second most successful treatment. The combination of Pyrethrum with Biofa achieved the highest efficacy and synergism and their efficacy approached that of the synthetic insecticide.